2020
DOI: 10.1002/ppsc.202000270
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Renal Clearable Inorganic Nanoparticles for Cancer Diagnosis

Abstract: (China). Her major research interest focuses on iron oxide nanoimaging probes and clinical conversion applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 164 publications
(214 reference statements)
0
9
0
Order By: Relevance
“…Kidneys eliminate small-sized nanoparticles by glomerular filtration, which is strictly dependent on the size, surface modification, morphology, and surface charge of the nanoparticles. 76 Here, BT NPs4 that possessed a smaller size could easily permeate through the fenestrated glomerular endothelium (pore diameter was ∼80− 100 nm) 77 and then preferentially accumulate in the kidney (Figures S29B and S30B). Further, the clearance efficiency of smaller-sized BT NPs4 was obviously higher than that of larger-sized BT NPs1 (1.54 vs 3.98 μg at day 4) (Figure S29C).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Kidneys eliminate small-sized nanoparticles by glomerular filtration, which is strictly dependent on the size, surface modification, morphology, and surface charge of the nanoparticles. 76 Here, BT NPs4 that possessed a smaller size could easily permeate through the fenestrated glomerular endothelium (pore diameter was ∼80− 100 nm) 77 and then preferentially accumulate in the kidney (Figures S29B and S30B). Further, the clearance efficiency of smaller-sized BT NPs4 was obviously higher than that of larger-sized BT NPs1 (1.54 vs 3.98 μg at day 4) (Figure S29C).…”
Section: Resultsmentioning
confidence: 94%
“…We observed that BT NPs1 with a relatively large size tended to accumulate in the liver (Figures S29B and S30A). Kidneys eliminate small-sized nanoparticles by glomerular filtration, which is strictly dependent on the size, surface modification, morphology, and surface charge of the nanoparticles . Here, BT NPs4 that possessed a smaller size could easily permeate through the fenestrated glomerular endothelium (pore diameter was ∼80–100 nm) and then preferentially accumulate in the kidney (Figures S29B and S30B).…”
Section: Resultsmentioning
confidence: 99%
“…When the hydrated particle sizes are less than 10 nm, nanomaterials will be quickly cleared by the kidney metabolism in the body. On the contrary, when the hydrated particle sizes are larger than 100 nm, nanomaterials are easily marked and eliminated by the immune system, which severely limits the bioavailability of the nanoparticles, thus affecting the imaging and therapeutic effects. , At the same time, when the reaction feed ratio is 6:1, the load rate of Fe­(III) is the highest, reaching 18% (Figure b). The content of Fe­(III) directly affects the MRI function, so the FePPy-NH 2 NPs obtained at a feed ratio of 6:1 were selected for subsequent experiments and show an average diameter of 54.3 nm under TEM (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…As such, it is anticipated that the ultrasmall luminescent nanoprobes will serve as potent PL imaging tools and provide a solution to in vivo imaging. [33][34][35] We should note that some specific challenges may also arise in the design and in vivo application of ultrasmall nanoprobes such as insufficient tumor targeting efficacy.…”
Section: Huanghao Yangmentioning
confidence: 99%
“…Even so, ultrasmall nanoprobes may have relatively low uptake in tumors than large-sized NPs due to their moleculelike renal clearance and fast blood clearance. 21,110,111 Impressively, some strategies have been presented to augment the tumor accumulation efficacy of ultrasmall nanoprobes. [112][113][114][115] For example, metal NPs can be synthesized in situ on template proteins (e.g., albumin), which may allow enhanced blood circulation and tumor accumulation effects than smallligand-capped counterparts (Fig.…”
Section: Ultrasmall Nanoprobes Versus Molecular and Large-sized Probesmentioning
confidence: 99%